Perception of Teachers about the Role of Parents in Developing Reading Habit of Basic Level Students - K.C., Kamala (Lumbini Journal of Language and Literature, 2022)
This study aimed to explore teachers’ perceptions about the role of parents in developing the reading habit of children to improve academic performance. In this qualitative study, semi-structured interviews were used for data collection, which enabled me in capturing qualitative experiences, opinions, beliefs, and perceptions of purposefully selected participants. The participants were three basic level English teachers from Rupandehi district, Lumbini Province, Nepal. Social constructivism of Vygotsky (1978) has been used as a theory in this study. The data were analyzed using a thematic analysis approach. The study confirmed that parents’ involvement is crucial in developing children’s reading habits. The parents’ continuous support in reading further enhances the academic performance of the children. The study helped me understand how children’s reading habits enable them to learn English from childhood, which thrives for further educational enhancement. It particularly appeals to and makes parents aware of their influential role in helping children begin reading habits at home.